Complete deficiency of adenine phosphoribosyltransferase: a third case presenting as renal stones in a young child. Issue 1 (January 1979) - Barratt, T M; Simmonds, H A; Cameron, J S; Potter, C F; Rose, G A; Arkell, D G; Williams, D I
Abstract : We report a third case of 2, 8-dihydroxyadenine stones in a child with a complete lack of the adenine salvage enzyme--adenine phosphoribosyltransferase (APRT). The propositus, a 20-month-old girl of consanguineous Arab parents, presented with multiple urinary tract infections and supposed 'uric acid' stones in the right renal pelvis and left ureter. Both parents and one brother were heterzygotes for the defect, in keeping with an autosomal recessive mode of inheritance. In contrast with the other purine salvage enzyme disorder of childhood with true uric acid stones (the Lesch-Nyhan syndrome), uric acid excretion was normal in all family members. As in our previous case, treatment with allopurinol, without alkali, has eliminated the urinary excretion of 2, 8-dihydroxyadenine: the stones were removed surgically. 2, 8-Dihydroxyadenine should be considered in any child thought to have uric acid stones and tests made to distinguish the two compounds.